A Mechanistic View of the Light-Induced Synthesis of Silver Nanoparticles Using Extracellular Polymeric Substances of Chlamydomonas reinhardtii - Rahman, Ashiqur (Molecules, 2019)
In the current study, extracellular polymeric substances (EPS) of Chlamydomonas reinhardtii and photon energy biosynthetically converted Ag(+) to silver nanoparticles (AgNPs). The reaction mechanism began with the non-photon-dependent adsorption of Ag(+) to EPS biomolecules. An electron from the EPS biomolecules was then donated to reduce Ag(+) to Ag(0), while a simultaneous release of H(+) acidified the reaction mixture. The acidification of the media and production rate of AgNPs increased with increasing light intensity, indicating the light-dependent nature of the AgNP synthesis process. In addition, the extent of Ag(+) disappearance from the aqueous phase and the AgNP production rate were both dependent on the quantity of EPS in the reaction mixture, indicating Ag(+) adsorption to EPS as an important step in AgNP production. Following the reaction, stabilization of the NPs took place as a function of EPS concentration. The shifts in the intensities and positions of the functional groups, detected by Fourier-transform infrared spectroscopy (FTIR), indicated the potential functional groups in the EPS that reduced Ag(+), capped Ag(0), and produced stable AgNPs. Based on these findings, a hypothetic three-step, EPS-mediated biosynthesis mechanism, which includes a light-independent adsorption of Ag(+), a light-dependent reduction of Ag(+) to Ag(0), and an EPS concentration-dependent stabilization of Ag(0) to AgNPs, has been proposed.